(untitled) (Revista de Medicina Clinica, 2025)
The International Olympic Committee (IOC) in 2014 changed the concept of the female athlete triad with the term energy deficiency in sport RED-S. This is a syndrome in which low energy availability impairs skeletal health due to the uncoupling of bone turnover, in which the rate of resorption increases while the rate of bone formation decreases. The result is progressive bone loss or the inability to accumulate bone mass, which increases the risk of stress fractures and osteoporosis. This case is about a 16-year-old female patient, who is a high-performance athletics athlete, with pain in the dorsum of the foot and heel, to rule out a Linsfranc joint injury, in addition to this with menstrual alterations that are amenorrhea and a percentage of body fat below what is allowed for her weight and height, the x-rays obtained of the foot and magnetic resonance imaging are discussed for the diagnosis in the patient.